Complementary feeding : building the foundations for a healthy life - Nestlé Nutrition Workshop 2016 : Singapore); Ahmed, Tahmeed; Aw, Marion; Black, Maureen M.; Black, Robert E.; Chan, Daisy; Makrides, Maria; Ong, Ken (Basel : Karger, 2017)
The complementary feeding period from 6 to 24 months is a crucial part of the first 1000 days of development. It marks the transition from exclusively milk-based liquid diet to the family diet and self-feeding. During this period, healthy food preferences and feeding practices are formed. The papers in this book were presented at the 87th Nestlé Nutrition Institute Workshop in Singapore, May 2016. Divided into three parts, they provide updates and recommendations, as well as insights into strategies and interventions, from all around the world. The first part addresses the role of complementary feeding in healthy development, focusing on food types and the timing of solid food introduction. The second part examines determinants of growth restriction and discusses effective interventions in infants and children in low- and middle-income countries. The last part focuses on development and 'programming' of behavioral and psychological aspects to prevent childhood obesity in high socioeconomic settings.
La función de los autores fue determinada por el catalogador
Keywords: NUTRICION DE LACTANTES -- CONGRESOS; DESARROLLO INFANTIL -- CONGRESOS